Recent changes in flood risk in the Gran La Plata, Buenos Aires province, Argentina : Causes and management strategy - Andrade, María Isabel (2007)
The paper analyses the causes of flood occurrence in the Gran La Plata, Buenos Aires Province, Argentina, and the changes that have occurred since the 1970s. The area is characterized by serious deficiencies in the use and management of water resources. The main factors are: (1) flood risk information is not updated; (2) urban building organization does not consider the flood risk; (3) the topography and other physical features are not taken into account in urban development. This research considers some specific problems, especially in data availability, and suggests ways to solve them, including improved analytical methodology. One of the main objectives is to analyse flood risk in social terms, producing a map of flood risk from the “human social vulnerability” point of view. The results suggest that flood risk has increased since the 1980s and that this is associated with changes in precipitation patterns that have also been aggravated by lack of controls on urban development. The poorer areas with the lowest level of infrastructure and public services, many of them developed over the last quarter-century, are especially vulnerable.